2017
DOI: 10.1016/j.matdes.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Variation of hardness, microstructure, and Laves phase distribution in direct laser deposited alloy 718 cuboids

Abstract: Property anisotropy and its unpredictability in direct laser-deposited material is a drawback to this additive manufacturing method. In this study, direct laser deposition was used to build threedimensional cuboids of Ni-based superalloy 718, which were examined with microscopy, and analyzed for hardness trends with contour mapping. Secondary electron and backscatter electron contrast imaging were used in conjunction with electron backscatter diffraction to understand microstructure. It is found that hardness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 38 publications
(70 reference statements)
8
20
0
Order By: Relevance
“…Figure 15. Box and whisker plot showing the variation in Vickers hardness of IN718 parts fabricated by AM and subjected to various post process heat treatments using data from [140,147,[184][185][186][187][188][189][190][191][192][193][194][195][196][197]. Figure 16.…”
Section: (D)mentioning
confidence: 99%
“…Figure 15. Box and whisker plot showing the variation in Vickers hardness of IN718 parts fabricated by AM and subjected to various post process heat treatments using data from [140,147,[184][185][186][187][188][189][190][191][192][193][194][195][196][197]. Figure 16.…”
Section: (D)mentioning
confidence: 99%
“…Researchers [8][9][10][11] studied strength variations within the weld region using Vickers hardness mapping technique and showed that it is a robust technique to quantify weld heterogeneity. A new homogenization technique to simplify a complex weld using slip line analysis was formulated in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were fabricated with a laser travel speed of 33 mm/s. The laser power was selected as 200W, 250W and 270W, producing linear energydefined as laser power (J) /laser travel speed (mm) [54]. Therefore the linear energy is 6.06 J/mm, 7.75 J/mm and 8.33 J/mm respectively.…”
Section: Lens As-printed Samples I) the First Batch Of Samplesmentioning
confidence: 99%